Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Kinerja UMKM pada UMKM Juara - Nuraeni, Delia Nurul; Dai, Ratna Meisa; Thirafi, Luthfi (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to determine the influence of financial literacy and financial behavior on the performance of MSMEs in UMKM Juara Majalengka Regency in 2023. The method used in this research is a quantitative method with a descriptive approach. This research uses primary data sources from a sample of 130 respondents and secondary data obtained from literature sources. The data collection technique is through a questionnaire that has passed validity and reliability testing with the results of the data used being valid and reliable. This research analyzes data using descriptive analysis and statistical analysis, namely classic assumption tests, multiple linear regression analysis and hypothesis tests (t test, F test and coefficient of determination). Based on the research results, the multiple linear regression equation formed is Y = 0.459 + 0.187 X1 + 0.512 X2. The results of partial hypothesis testing, namely the t test, are 1) financial literacy has a positive and significant influence on the performance of MSMEs 2) financial behavior has a positive and significant influence on the performance of MSMEs. The results of hypothesis testing carried out simultaneously, namely the F test, showed that financial literacy and financial behavior had a significant positive influence on the performance of MSMEs. The percentage of influence exerted by the independent variables, namely financial literacy and financial behavior, on the dependent variable, namely the performance of MSMEs, is 49.8% and the remaining 50.2% is influenced by other variables or things that the researchers ignored.